The Use of Personal Inarisk Media in Improving the Concept of Disaster Information Literacy in social Studies Learning - Kurniawan, Nia; Mulyana, Eldi; Nopharipaldi Rohman, Slamet; Widyanti, triani; Tetep; Supriyatna, Asep; Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2020)
The purpose of this study is to determine the improvement of the concept of disaster information litera cy using InaRisk Personal lea rning media in socia l studies learning. This research approa ch uses quantitative with quasi-experimenta l method with nonquivqlent control group design. The population of this resea rch is the seventh grade students of SMP Negeri 1 Ta rogong Ka ler. The sample wa s taken by purposive sampling technique with cla ss VII A as the experimental cla ss and class VII B as the control class. Based on the results of statistical ana lysis, the Asymp.sig.2-tailed value is 0.000 and a is 0.05, which means 0.000 <0.05, then Ho is rejected. From these data it can be concluded that the value of Asymp.sig. of 0.000 < 0.05, then there is a significant increase or lea rning that uses InaRisk Personal lea rning media is effective to be applied. Overa ll, the ability of the concept of disaster information litera cy affects the prepa redness of students in dealing with disasters in the surrounding environment. the ability of the concept of disaster information literacy in the experimental cla ss increased significantly in terms of seeking information, identifying information, evaluatinginformation, andusinginformation.